Mitoepigenetics and gliomas: epigenetic alterations to mitochondrial DNA and nuclear DNA alter mtDNA expression and contribute to glioma pathogenicity - Grady, Clare I.; Walsh, Lisa M.; Heiss, John D. (Frontiers in Neurology, 2023)
Epigenetic mechanisms allow cells to fine-tune gene expression in response to environmental stimuli. For decades, it has been known that mitochondria have genetic material. Still, only recently have studies shown that epigenetic factors regulate mitochondrial DNA (mtDNA) gene expression. Mitochondria regulate cellular proliferation, apoptosis, and energy metabolism, all critical areas of dysfunction in gliomas. Methylation of mtDNA, alterations in mtDNA packaging via mitochondrial transcription factor A (TFAM), and regulation of mtDNA transcription via the micro-RNAs (mir 23-b) and long noncoding RNAs [RNA mitochondrial RNA processing (RMRP)] have all been identified as contributing to glioma pathogenicity. Developing new interventions interfering with these pathways may improve glioma therapy.